Assessing the value of medicinal innovation in an era of increasing austerity - Geitona, Mary (Social Cohesion and Development, 2016)
In this paper an overview of the rewarding innovation pharmaceutical regulatory systems has been presented, focusing on the emerging role of innovation and health technology assessment (HTA). Ιn a time of political and financial turmoil, benefits could be obtained through the pooling of resources and experiences among various countries. For this purpose, recent major pharmaceutical reforms in Greece have been critically discussed taking into consideration the dynamic and complex environment among cost containment measures and the recent implementation of HTA in combination with some of the critical factors that influence today’s key decision makers, such as the economic crisis, increasing austerity as well as political and international pressures.